Tata Kelola Perusahaan dan Penghindaran Pajak: Eksplorasi dalam Konteks Indonesia - Aditya Danang Saputra; Riyan Surya Wibowo; Muthohirin Muthohirin; Daniel Kassim Sesay; Ibrahim Rahman Turay (Inovasi Analisis Data, 2024)
This research examines the relationship between corporate governance and tax avoidance in non-financial firms listed on the Indonesia Stock Exchange from 2020 to 2023. Corporate governance factors such as the composition of the audit committee, proportion of independent directors, executive compensation, public ownership, and largest shareholding were analyzed. Tax avoidance was assessed using a performance-adjusted measure. The findings, derived from ordinary least squares regression analysis with controls for year and industry sector effects, reveal that public ownership and largest shareholding negatively influence tax avoidance, whereas firm performance positively affects it. However, the expertise background of the audit committee, proportion of independent directors, executive compensation, and firm size did not demonstrate significant impacts on tax avoidance. These results suggest that certain corporate governance mechanisms in Indonesia may not effectively serve shareholders' interests.